Pengaruh Saving Intention Terhadap Lifestyle Encouragement Melalui Digital Accessibility - Nadya Debora Siregar; Sugeng Suroso; Achmad Fauzi (CV. ITTC INDONESIA, 2026)
The digitalization of financial services has reshaped the saving intention of young people in Indonesia. Easier access to mobile banking, e-wallets, and fintech platforms simplifies saving activities while also encouraging consumptive tendencies influenced by digital lifestyles. Previous studies have largely examined saving intention from a conventional perspective and have rarely positioned digital accessibility as a variable that connects these two contrasting effects. This study aims to examine the effect of saving intention on lifestyle encouragement, with digital accessibility as an intervening variable among young users of digital financial services in Indonesia. This study employed a quantitative approach with an explanatory research design and a cross-sectional design. Primary data were collected through an online questionnaire from 200 respondents aged 18-40 years using a purposive sampling technique, then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that saving intention has a positive and significant effect on digital accessibility and lifestyle encouragement. Digital accessibility also has a positive and significant effect on lifestyle encouragement and is proven to mediate the relationship between saving intention and lifestyle encouragement. The research model explains 15% of the variance in digital accessibility and 38.7% of the variance in lifestyle encouragement. These findings indicate that digital accessibility plays a dual role in shaping the financial behavior of young people and should therefore be utilized wisely to support long-term financial goals while reducing excessive consumptive tendencies.